Serum-free production of mAbs: from flask cultivation to perfusion bioreactor cultivation - Bengtsson, Johannes (My University, 2022)
Monoclonal antibodies (mAbs) are known for their binding affinity and specificity to specific epitopes of an antigen, allowing for various applications in therapeutics and diagnostics. Today, most mAbs are produced from hybridoma cell lines developed by the hybridoma technique introduced by Köhler and Milsten in 1975(1). Fujirebio Diagnostics AB (FDAB) Gothenburg, Sweden, is a company in close contact with the in vitro diagnostics industry. FDAB specialises in production of monoclonal antibodies and antigens, sold both separately and in prepared test kits. This project contributes to an ongoing project at FDAB with the objective to cultivate mAbproducing hybridoma cells serum-free in perfusion bioreactors. A serum-free production ensures a stable production of mAbs independent on serum availability and/or quality. Cultivation in perfusion reactors intends to scale up the production to a controlled environment with high antibody productivity. In this project, hybridoma cells producing mAbs named E146 are adapted to two commercially available serum-free media from Gibco, namely Chemically Defined (CD) Hybridoma and Hybridoma Serum-Free Medium (SFM). Furthermore, the project evaluates if hybridoma cells producing mAbs named C192 are cultivable in a stirred-tank perfusion bioreactor. Downstream processing for quality control and characterisation of E146/C192 mAbs includes procedures/methods such as purification, size exclusion chromatography (SEC), immunoactivity assay, and isoelectric focusing (IEF). The results show that E146-producing cells cultivated in CD Hybridoma allow for higher specific antibody productivity (pg mAb cell-1 day-1) compared to standard medium and Hybridoma SFM. It is however to be elucidated whether a discovered change in charge distribution among the charge isoforms of E146 affect the quality of the product. E146-producing cells are cultivable in Hybridoma SFM as well but was not a favourable medium from an economical or specific antibody productivity point of view. The bioreactor cultivation of C192-producing cells encountered various difficulties, such as aggregation and cellular degradation. Aggregation occurred after rapid transitions from log phase to stationary phase and decline phase. Therefore, closer monitoring and regulation of cell specific perfusion rate (CSPR) is suggested to further investigate what causes cell aggregation. Furthermore, a change in charge distribution is seen for charge isoforms of C192 as well, but it does not affect the antigen-antibody binding ability of the mAbs.
Keywords: Monoclonal antibodies; hybridoma cells; serum-free culture medium; stirred-tank perfusion bioreactor